Trapper: an open source web‐based application to manage camera trapping projects. Issue 10 (24th May 2016) - Bubnicki, Jakub W.; Churski, Marcin; Kuijper, Dries P. J.
Summary: Camera trapping is increasingly becoming an important tool in ecological research. However, the organization of large collections of multimedia files and especially efficient searching for subsets of data is a challenging task. While the development of project‐specific software solutions is dominating in the camera trapping community, little attention has been paid to more flexible and open‐source solutions supporting diverse camera trapping research projects. We used state of the art and well‐recognized open source software components and programming language python to design and implement trapper, a flexible data base driven web application to manage, classify, integrate, share and re‐use data in camera trapping projects. The main features of trapper are: (i) it is fully open‐source, (ii) it facilitates analysis of videos as well as images, (iii) it provides spatial filtering and web‐mapping, (iv) it allows flexible implementation of specific data collection protocols, (v) it is a multi‐user and role based system which facilitates collaborative work on camera trapping projects, (vi) it supports data re‐use and (re)discovery. trapper can therefore be widely used by ecologists working with a variety of camera trap studies, alone or in collaboration with each other.